Diagnostic Significance of Haemogram Parameters and RBC Indices in Haemoglobin E Trait - Khondaker, Tarannum; Ahmed, Abul Kashem Jalaluddin; Amin, Syed Khairul (Anwer Khan Modern Medical College Journal, 2017)
Background: Hemoglobin E disease are the most common structural haemoglobinopathies, reaching its highest frequency in South East Asia and also prevalent in Bangladesh. There are very few data for effective screening of HB E trait. The aim of the study was to analyze hematological profile and RBC indices as a marker of screening for Hb E trait. Methodology: A cross sectional observational study was conducted among 150 subjects at Dhaka Shishu (Children) Hospital from December 2008 to November 2009. On the basis of Hb electrophoresis, all subjects were divided into three groups. Group I comprised of 50 subjects with Hb E trait, group II comprised 51 subjects with ß thalassemia trait and Group III comprised of 49 normal subjects. Result of RBC indices and blood count were compared between Hb E trait and normal study population. Results: In group I the mean age was 29.53 years and the age range was 2-47 years. In group II the mean age was 30.31 years and the range was 1-55 years. In group III the mean age was 21.81 years and the range was 1-52 years. The present study revealed the mean±SD haemoglobin level (g/dl) in group I (E trait) and group III (normal subjects) were 11.76±1.91 and 10.77±1.4 respectively. Statistically no significant difference was found between these 2 groups (P>.05). The mean corpuscular volume (MCV) in mean±SD in group I and group III were 72.89±12.24 fl and 77.35±10.27 fl respectively. No statistical significance was found as P>0.05. The mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) in group I were 24.84±2.71pg & 32.97±2.27 g/dl and in group III were 28.28±2.71 pg & 32.97±2.38 g/dl respectively. There were no significant difference between group I and III regarding MCH and MCHC.The mean RBC count in E trait and normal subject group were 5.01±71 million/cmm and 4.61±0.65 million/cmm respectively. There was no significant difference was found P>0.05. Mean red cell distribution width (RDW) in group I and III were 14.32 ±2.34 and 14.83±1.28 without any statistical difference (P>0.05) Conclusion: In our study there were no diagnostic significance of Blood count and RBC Indices for detection of Hb E trait. More study should be conducted to find out reliable marker of screening for Hb E carrier. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 94-99